Addressing tagging location bias to assess space use by marine animals. Issue 10 (9th August 2020) - Hays, Graeme C.; Rattray, Alex; Esteban, Nicole
Abstract: Estimates of space use derived from animal tracking studies are often biased by where animals are tagged, with areas distant to the tagging site, in both space and time, being under‐represented. We develop an approach to overcome this tagging bias by quantifying the likely movements of animals after tags have failed. We illustrate the approach using high accuracy Fastloc‐GPS tracking data for 35 adult female green turtles Chelonia mydas equipped with satellite tags within one of the world's largest marine protected areas (MPAs), the British Indian Ocean Territory (BIOT) MPA. Individuals migrated up to 5, 127 km from the tagging site, breaking migration distance records for this species. For 28 of the 35 individuals travelling to foraging locations well outside the MPA, we estimated that they spent, on average, 9.8% of their adult lives within the BIOT MPA. Synthesis and applications . We highlight the importance of the British Indian Ocean Territory marine protected area (MPA) as a nesting sanctuary for turtles from across an ocean basin. The general approach outlined here can be applied to a broad range of taxa, including marine mammals, fish and sea turtles and will allow unbiased estimates of how important areas, such as MPAs, are used. Abstract : We highlight the importance of the British Indian Ocean Territory marine protected area (MPA) as a nesting sanctuary for turtles from across an ocean basin. The general approach outlined here can be applied to a broad range of taxa, including marine mammals, fish and sea turtles and will allow unbiased estimates of how important areas, such as MPAs, are used.